English and Semiotic Elements in Local Product Packaging: Consumer Interpretation and Purchase Intention - Alfridha Dwi Putri; Jamaluddin Gesrianto A'ban; Fisma Fisma (Universitas Negeri Makassar, 2026)
This study investigates the role of English and visual semiotic elements in shaping consumer perception and purchase intention toward local food product packaging in Bulukumba, Indonesia. The research focuses on local snack and culinary packaging that combines English and Indonesian textual elements with visual components such as color, logos, and images. Using a mixed-method approach, the study combined quantitative survey data with qualitative Focus Group Discussions (FGD). Quantitative data were analyzed using descriptive statistics and Chi-Square analysis through SPSS version 30.0, while qualitative data were analyzed using thematic analysis within a multimodal semiotic framework based on the perspectives of Saussure, Peirce, and Barthes. The findings reveal that English in local product packaging functions primarily as a symbolic resource rather than solely as a communicative medium. Although many respondents demonstrated limited comprehension of English text, they still associated English-language packaging with modernity, prestige, and higher product quality. Visual elements such as color, logos, and imagery also significantly influenced consumer perception by creating emotional and sensory associations. The study further demonstrates that textual and visual elements operate complementarily, where English provides symbolic legitimacy and aspirational identity, while visual elements generate emotional engagement and product attractiveness. Furthermore, bilingual packaging combining English and Indonesian was perceived as more effective because it balances global appeal with local accessibility and cultural familiarity.